A novel technique for external iliac artery reconstruction in renal transplant patients with extensively atherosclerotic lower limb vasculature - Daanish Sheikh, BS; Shri Timbalia, MD; Mahnoor Zia, MD; Yusuf Mufti, BS; Maham Rahimi, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
We describe a 54-year-old man with type 2 diabetes mellitus, ischemic myopathy, pulmonary hypertension, and end-stage renal disease who was admitted for heart failure and listed for a dual cardiac-renal transplantation. Extensive calcification in the iliac arteries prevented clamping. Proximal endovascular balloon control of the left iliac artery was achieved using contralateral access; distal control was established by passing a Fogarty catheter distally through an iliac arteriotomy, later used for anastomosis of the cadaveric conduit. Postoperative Doppler imaging confirmed adequate renal perfusion. The patient was discharged in stable condition. This report presents a novel one-stage intravascular occlusion method for calcified arteries.